2016
DOI: 10.21037/jtd.2016.05.77
|View full text |Cite
|
Sign up to set email alerts
|

Exophiala pisciphila: a novel cause of allergic bronchopulmonary mycosis

Abstract: Allergic bronchopulmonary mycosis (ABPM) is a hypersensitivity reaction to fungal antigens, which may particularly plague uncontrolled asthmatics. Non-aspergillus fungal organisms may be implicated and may elicit a more severe immunologic response. Exophiala pisciphila, a marine organism, has not been reported as a culprit yet. However, this report indicates it may be implicated in unrelenting symptoms in a severe asthmatic patient who had become dependent on corticosteroids. Proper identification and adequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Yeasts grow in a wider pH range (between 5 and 6) [44,45], which could explain their abundance in NT and CT soils. Herpotrichilaceous fungi have been identified in low relative abundance (Figure 2), which include Rhinocladiella aquaspersa, a rare agent of chromoblastomycosis [46]; Exophiala pisciphila, associated with infection in cold-blooded animals [47], although in isolated cases, it can infect humans [48]; and E. dermatitidis an opportunistic pathogen that causes peritonitis [49], cystic fibrosis, phaeohyphomycosis, and chromoblastomycosis in humans [50].…”
Section: Discussionmentioning
confidence: 99%
“…Yeasts grow in a wider pH range (between 5 and 6) [44,45], which could explain their abundance in NT and CT soils. Herpotrichilaceous fungi have been identified in low relative abundance (Figure 2), which include Rhinocladiella aquaspersa, a rare agent of chromoblastomycosis [46]; Exophiala pisciphila, associated with infection in cold-blooded animals [47], although in isolated cases, it can infect humans [48]; and E. dermatitidis an opportunistic pathogen that causes peritonitis [49], cystic fibrosis, phaeohyphomycosis, and chromoblastomycosis in humans [50].…”
Section: Discussionmentioning
confidence: 99%
“…mycoses are occasionally reported (Hjeltnes et al, 2019), but the species is not always identified. It has also been suggested that some species, such as E. pisciphila and E. salmonis, might have potential as zoonotic pathogens (Revankar & Sutton, 2010;Yoon et al, 2012;Kebbe & Mador, 2016). The Table 2 sums up the occurrence of known fungal pathogens in the fish species.…”
Section: Fungimentioning
confidence: 99%
“…pisciphila and E . salmonis , might have potential as zoonotic pathogens (Revankar & Sutton, 2010; Yoon et al, 2012; Kebbe & Mador, 2016). The Table 2 sums up the occurrence of known fungal pathogens in the fish species.…”
Section: Diseases Of Lumpfish and Wrassementioning
confidence: 99%
“…Exophiala pisciphila: Un hongo dematiáceo marino (color oscuro) perteneciente a la familia de las levaduras negras. Fue descrito por Carmichael en 1966, desde entonces, se ha implicado como causa de micosis sistémica en varias especies de peces(26).…”
unclassified